Research methods in education : - Wiersma, William (Pearson, 2005)
A classic in its field, Research Methods in Education explores quantitative and qualitative research from beginning to end, starting with the formulation of a research question straight through to publication. Retaining the clear, concise writing style and organization that has made this text so popular, Research Methods in Education helps readers evaluate research literature as well as master research methodology. It emphasizes the rationale for commonly used research procedures and their applications. The authors outline the nature of educational research and the clearly define the steps in the research process. Research Methods in Education gives readers a solid understanding of all the elements of research. The text is broad in scope ' covering both quantitative, qualitative and mixed methods research methodologies as well as sampling designs, measurement, data collection, preparation of data sets for computer analysis, statistical procedures, and reports. Research Methods in Education gives students a solid understanding of all the elements of research.